Resolving the ambiguity: A meta-analysis of the effect of employment protection on employment and unemployment - Johanna Kemper (ETH Zurich, KOF Swiss Economic Institute, 2016)
The effect of employment protection legislation (EPL) on unemployment and employment levels is still an unresolved issue in the literature. To tackle this issue is the aim of this meta-analysis. Drawing on evidence from 72 studies, I find that EPL has no statistically significant effect on the unemployment level. Based on 42 studies, I find that EPL decreases the employment level. Analysing study hetero- geneity reveals that the quality of the identification strategy matters for the results. In particular, studies that account for unobserved heterogeneity across countries or exploit variation at the country level confirm the main findings of the meta-analysis.
Keywords: J8; J20; J21; J65; C49; 330; Employment Protection Legislation; Unemployment; Employment; Meta-Analysis